2009
DOI: 10.1177/0145482x0910300805
|View full text |Cite
|
Sign up to set email alerts
|

Use of Assistive Technology by Students with Visual Impairments: Findings from a National Survey

Abstract: This study investigated the use of assistive technology by students in the United States who are visually impaired through a secondary analysis of a nationally representative database. It found that the majority of students were not using assistive technology. Implications for interventions and potential changes in policy or practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 8 publications
2
36
0
1
Order By: Relevance
“…Formal training is also likely to help reduce the gaps caused by socioeconomic status and other opportunity and resource-related factors. The lack of formal training is also an issue in urban areas in high GDP per capita countries [6,15]. Perhaps the international community may contribute positively to this situation by designing updated training materials that are made available to all people in similar situations around the world?…”
Section: Smartphone Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Formal training is also likely to help reduce the gaps caused by socioeconomic status and other opportunity and resource-related factors. The lack of formal training is also an issue in urban areas in high GDP per capita countries [6,15]. Perhaps the international community may contribute positively to this situation by designing updated training materials that are made available to all people in similar situations around the world?…”
Section: Smartphone Practicesmentioning
confidence: 99%
“…However, the lack of assistive technology use is not unique to low GDP per capita countries. A study from 2009 of visually impaired students in the US [6], which can be classified as a high GDP-per-capita region (world rank 10 in 2020 according to IMF), showed that a majority (more than half) did not use any software-based assistive technology. Moreover, these visually impaired students were not being trained to use assistive technologies in schools, contrary to what the professionals assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Thurlow, Johnstone, Timmons and Altman (2009) found a pressing need for technology-based reading assessment for the visually impaired in the U.S. Kelly (2009) investigated the use of assistive technology by visually impaired students in the United States. Findings show that a majority of these students were not using assistive technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of Adaptive Technology in VIP learning may still be considered modest. In the USA, for instance, only 59% of the 71% of VIP students (able to use this kind of technology) have a factual opportunity to do this [4]. Adaptive Technology has had an unimportant role in the whole education process due to two important factors: high cost, and small number of teachers who really bring significance to its use in actual classrooms.…”
Section: Adaptive Technology and Vip Learningmentioning
confidence: 99%
“…Diminishing (1) from (2) gives (3), which can be rewritten as (4). The final value of S (5) is the summation representing Sissa's reward.…”
mentioning
confidence: 99%